Wahdat AL Ulum and Academic Ethics - Nopita Sari Ritonga; Akbar Siregar; Suci Ramadhani Saragih; Rhamadhani; Mahira Salsabila (ISNU Sumatera Utara, 2025)
Wahdat al-'ulum teaches that no knowledge is value-free. Every knowledge should bring humans closer to their Creator and encourage the creation of a just and moral civilization. Therefore, this approach is highly relevant to the education system, especially in universities, which are the breeding ground for various branches of knowledge. Within this framework, wahdat al-'ulum is not only a philosophical concept but also a foundation for shaping the character of academics with integrity, honesty, and social and spiritual responsibility. This definition implies that knowledge is the knowledge possessed by a subject about an object that is true. The truth contained in this knowledge is correspondence, because there is a match between the subject's knowledge and the objective conditions of the object being known. There are two ways to know an object correctly. The first is through the subject's observation of the object. In observing objects, humans have different methods and abilities, so the accuracy of the results varies. The better the tools used and the higher the capabilities of the tools used to observe the object, the more accurate the knowledge obtained. This kind of knowledge is referred to as knowledge obtained through reason.